Pre-Service English Teachers’ Ability in Applying Teaching Skills - Nur Inda Astuti Mabing; Rasuna Rasid Talib; Nurlaila Husain (Jambura Journal of English Teaching and Literature, 2022)
ABSTRACT Basic teaching skills are complex skills, which must be possessed by an educator and be able to apply them in the learning process. These basic teaching skills include opening and closing lessons, questioning skills, explaining skills, variation skills. The purpose of this study was to determine how the application of basic teaching skills during the teaching practice experience exam. This research was conducted using qualitative methods. The subjects of this study were 5 students teaching practice experience. The data collection technique in this study used an observation sheet by viewing the video exam for students teaching practice experience. Based on the results of video observations by researcher regarding the application of basic teaching skills in the teaching practice experience class, the basic teaching skills are quite good and effective because in general the participants in the teaching practice experience have applied the four basic teaching skills well but not all of the points contained in these skills implemented at the time of teaching. But in this case it can be overcome thanks to the cooperation between teachers and students.